Pembelajaran Kontekstual Sebagai Strategi Dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik: Kajian Literatur - Andi Sri Wahyuni Mumang (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
Abstract: Nowadays, teachers in the learning process still tend to use methods only based on transferring knowledge in theory. This means that students do not know much about the meaning of the lessons given. This research is descriptive research that aims: to analyze and explain contextual learning as a strategy in improving students' critical thinking abilities and to determine the effectiveness of contextual learning as a strategy in improving students' critical thinking abilities. The research method used by the researcher is a literature review study, the researcher looks for relevant information from various book and journal sources regarding the discussion and provides a systematic explanation regarding the results of the analysis which are described descriptively. The research results show that contextual learning as a strategy can provide students with the opportunity to develop their insight into the material being studied and relate it to everything real in everyday life. Contextual learning as a strategy allows students able to develop the potential to think critically about the material provided. Therefore, contextual learning can be an effective strategy used in the learning process. This learning model can foster students' critical thinking skills so that learning objectives can be achieved.